1976
DOI: 10.1021/bi00670a026
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of triosephosphate isomerase: the fate of the 1(R)-3H label of tritiated dihydroxyacetone phosphate in the isomerase reaction

Abstract: The isomerization of specifically tritium-labeled [ 1 (R)-3H]dihydroxyacetone phosphate to D-glyceraldehyde 3-phosphate, catalyzed by the enzyme triosephosphate isomerase, has been studied. The distribution of the 3H label amongst the three possible sites (in [ 1 (R)-3Hldihydroxyace-tone phosphate, in ~-[2-~H]glyceraldehyde 3-phosphate, and in the solvent) has been followed as a function of the extent of the reaction. It is shown that the extent of transfer of the 3H label from the substrate dihydroxyacetone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 16 publications
5
93
1
Order By: Relevance
“…As much as 50% intramolecular transfer of proton from GAP to DHAP and Ϸ18% from DHAP to GAP were documented. The later is considerably higher than the Ͻ6% detected by radioactivity and mass spectral analysisbased assays (3,25). Notably, the same study also found that partitioning of the endiol(ate) depends on the substrate identity; the reaction of the two substrates is not likely to share a common, single intermediate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As much as 50% intramolecular transfer of proton from GAP to DHAP and Ϸ18% from DHAP to GAP were documented. The later is considerably higher than the Ͻ6% detected by radioactivity and mass spectral analysisbased assays (3,25). Notably, the same study also found that partitioning of the endiol(ate) depends on the substrate identity; the reaction of the two substrates is not likely to share a common, single intermediate.…”
Section: Discussionmentioning
confidence: 89%
“…The precise path of the transferred proton and the identity of the reaction intermediates have been, by and large, deduced from the fate of isotopic labels (1,2). The existence of a stable enediol(ate) intermediate has been inferred from the loss of an isotope label from the substrate during the reaction (1,3); this reaction intermediate must exist with a sufficient lifetime to allow partial equilibration of the catalytic base with the surrounding solvent. Moreover, when the reaction takes place in tritiated water the solvent's tritium is incorporated into both the substrate and product, evidence that the hydrogen of the newly formed carbonhydrogen bond is mostly derived from the solvent (4,5) and that exchange occurs from an enzyme bound intermediate.…”
mentioning
confidence: 99%
“…A well known example is that of Knowles et al . where the FEP for TIM was partially defined using various isotopic measurements (1, 2, 33, 6062). Other notable examples include work by Knowles et al .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycolohydroxamate [bis(cyclohexylammonium) salt] was synthesized by Dr. J. G. Belasco as described in Belasco and Knowles (1980). [ 1 (R)-3H] Dihydroxyacetone phosphate (9 Ci/mol) was prepared by Dr. R. T. Raines according to the method of Herlihy et al (1976). Phospho-[l-I4C]glycerate (14.1 Ci/mol) was prepared by Dr. D. L. Pompliano according to the method of Guilford et al (1987).…”
Section: Methodsmentioning
confidence: 99%